Islamic Circular Economy in Business Practice and Islamic Finance: A Systematic Literature Review - Fathma, Azizah; Thoriq Alfarisi, Muhammad; Darwanto (Journal of Islamic Economic Laws, 2025)
Global environmental crises, including climate change, natural resource degradation, and increasing waste, pose significant challenges to conventional linear economic systems. In response, the circular economy has emerged as an alternative model emphasizing resource reduction, reuse, and recycling. However, scholarly work examining its integration with Islamic values remains fragmented. This study addresses this gap through a systematic literature review of 11 Scopus-indexed publications (2019-2024) conducted according to PRISMA guidelines. The method employed in this research is a literature review, which aims to describe the existing research landscape on the circular economy from an Islamic perspective, drawing on relevant and current academic literature. The analysis reveals two themes in circular economy research from an Islamic perspective: First, the concept of Islamic Circular economy in business practice, such as khalifah fil ardh (stewardship), tawazun (balance), maslahah (public benefit), and the prohibition of israf (waste), demonstrates intrinsic compatibility with circular economy goals. Second, the Islamic finance sector, with its blended financial models, Islamic social finance instruments, and green sukuk, offers viable financing alternatives for circular economy initiatives. The findings provide a foundational mapping for future research to further develop Islamic circular economy models, particularly through empirical validation and practical implementation strategies in both financial and business domains.